Implementasi Plugin Notifikasi Sebagai Media Integrasi Antara E-Learning Moodle dengan BOT Telegram (Studi Kasus : Bimbingan Belajar The Second School) - Renaldi Muhammad; Issa Arwani; Bayu Rahayudi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Currently e-learning Moodle is a website that is often used to support the learningprocess, one of which is the Tutoring called The Second School. In the tutoring there are activities undertaken by the theacer such as announcement, material upload, and assignment. Then the teacher will notify manually via whatsapp group. However, from the above process, there is a problem faced by the teacer, namely when sending notifications of activities on e-learning is still done manually by sending notification to each class and whatsapp group. Based on the above problems, the researcher will implement the notification plugin as a medium of integration between Moodle e-learning and Telegram BOT. This study uses Telegram rather than Whatsapp because Telegram is equipped with BOT facilities which can be integrated into many applications one of which is e-learning Moodle which is used in tutoring The Second School. The purpose of implementing this notification plugin is expected to help teachers send notifications of announcements and students get notifications from Moodle e-learning through the Telegram application. The results obtained from the blackbox testing testing the implementation of the notification plugin as a medium of integration between Moodle e-learning and Telegram BOT can run as evidenced by the inclusion of notifications in Telegram after the announcement on Moodle e-learning. Furthermore, the results of the usability test using SUS get an average score of 74 in the category of Good and Grade Scale C, which means acceptable or acceptable in the acceptability ranges category.